Synthesis of metallophosphaalkenes by reaction of organometallic nucleophiles with a phosphaethynolato-borane - Wilson, D; Goicoechea, J (Royal Society of Chemistry, 2019)
We describe the reaction of a phosphaethynolato-borane [B]OCP ([B] = N,N′-bis(2,6-diisopropylphenyl)-2,3-dihydro-1H-1,3,2-diazaboryl) with the organometallic nucleophile Na[Cp*Fe(CO)2] (Cp* = pentamethylcyclopentadienyl). The electrophilic character of [B]OCP allows for a new route towards the formation metal–phosphorus bonds affording a metallophosphaalkene that can be functionalised at both the oxygen and phosphorus atoms depending on the reagents employed.